In-situ trace element and S isotope systematics in pyrite from three porphyry-epithermal prospects, Limnos Island, Greece - Börner, Frederik; Keith, Manuel; Bücker, Jonas L.; Voudouris, Panagiotis; Klemd, Reiner; Haase, Karsten; Kutzschbach, Martin; Schiperski, Ferry (Frontiers in Earth Science, 2022)
Porphyry-epithermal systems associated with high-K calc-alkaline to alkaline igneous host rocks may be prospective for the recovery of Te among related elements like Cu, Ag, and Au. Limnos Island, as part of the Tethyan magmatic belt, is such an example, where (telescoped) porphyry-epithermal mineralization is accompanied by different alteration-styles reflecting various hydrothermal processes. Here, we present in-situ S isotope and trace element data of pyrite, which records the fluid evolution from the early porphyry to the late epithermal stage in three distinct prospects (Fakos, Kaspakas, Sardes) on Limnos Island. Pyrite in the sericitic alteration of Fakos mainly formed from single-phase magma-derived fluids lacking evidence for phase separation, as reflected by relatively constant 34S (about -4‰) and Co/Ni (0.1-1) values. By contrast, in the sericitic alteration of Kaspakas and the following epithermal stages, an influence of boiling is implied by negative 34S values to -15‰, significant intergrain 34S variations (>3‰), highly variable Co/Ni (100-0.01) and As/Co (10-0.001) in pyrite. Higher 34S values (above -4‰) in porphyry pyrite from Sardes and partly in the other two hydrothermal systems are related to mixing between magmatic S, and S which was transported through deeply circulated seawater and/or meteoric water. We propose that fluid-rock interaction buffered the pH to higher values, which enhanced the solubility of Au and Te. Subsequent boiling processes caused the Au deposition, whereas Te partitioned into the vapor and finally precipitated upon condensation into meteoric water. This process is accompanied by continuous cooling during fluid ascent from 780 °C to <300°C, as indicated by increasing Sb, Tl, and Pb in pyrite from the porphyry to the epithermal stage. Consequently, the in situ 34S and trace element analysis allows to constrain the depositional environment of economic metals like Au and Te in porphyry-epithermal prospects.